Experimental and Statistical Analysis of Effect of Si Modification and Grain Refinement on Tensile Properties of A356 Alloy - Uludağ, Muhammet (Gazi Universitesi, 2021)
The focus point of recent research on light metal castings has been on the effect of casting quality on the material properties and maximizing the quality is the most important factor toward obtaining the best properties from an alloy. Sr additions modify Si morphology while grain refiners such as AlTixBy and Ti-free B make dendrite arms smaller in the alloy. Therefore, this study has been performed to evaluate the relationship between casting quality and tensile properties of A356 alloy. The modification and refinement treatments were carried out with three different master alloys: AlSr15, AlTi5B1, and AlB3. The tests were conducted under two conditions: with and without degassing to evaluate the effect of change in melt quality. Results obtained from experimental studies were analyzed statistically. It was concluded that there is a good relationship between bifilm index and tensile test results when the bifilm index is divided into three groups, namely: poor, medium and high quality. It was found that while Ti grain refinement addition positively affects the mechanical properties, Sr addition has a negative effect on casting quality.
Keywords: degassing; A356 alloy; A356 alloy; modification; grain refinement; Weibull analysis; bifilm index